2022
DOI: 10.1111/vde.13130
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the diagnostic performance of prick test with two environmental allergens in dogs with atopic dermatitis: A study using intradermal test as the gold standard

Abstract: Background There are no studies investigating the correlation between prick test (PT) and intradermal test (IDT) with environmental allergens in dogs with atopic dermatitis (AD). Objectives To investigate the correlation between PT and IDT for two environmental allergens, and to calculate the sensitivity, specificity and Youden index of PT, using IDT as the gold standard. Materials and methods Twenty‐two dogs with AD were selected. PT was performed with glycerinated allergen extracts, along with negative and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…However, we have documented an overall marginal (47%) sensitivity for SPT (graded subjectively). A recently reported study showed even lower sensitivity (0%) when SPT and IDT reactions to two environmental allergens ( D. farinae and Lolium perenne ) were compared 11 . Although SPT fared better in our study, with sensitivities ranging from a high of 63% for dust mite mix and grass pollen mix to a low of 8% for mould mix no.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…However, we have documented an overall marginal (47%) sensitivity for SPT (graded subjectively). A recently reported study showed even lower sensitivity (0%) when SPT and IDT reactions to two environmental allergens ( D. farinae and Lolium perenne ) were compared 11 . Although SPT fared better in our study, with sensitivities ranging from a high of 63% for dust mite mix and grass pollen mix to a low of 8% for mould mix no.…”
Section: Discussioncontrasting
confidence: 75%
“…A recently reported study also documented very good specificity for SPT (>94%). 11 On balance, it is the poor sensitivity of SPT documented by these two studies that will require further investigation if veterinary allergists continue to be interested in utilising SPT in dogs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations